Aspectos socioambientais de áreas costeiras com potencialidade aquícola no município de Niterói - RJ - Ferraz, Geovani Merchioratto (2009)
A great part of Brazilian coast has potential for shellfish growing due to its geographical localization, climate and water quality. This work aims to evaluate sanitary and social aspects of coastal environments with mussel culture potential, in the city of Niterói RJ. The Itaipu and Jurujuba inlet mussel culture and fishing communities social actors perception have been analyzed and compared, in relation to diseases originated from seafood and water and yet in relation to the mussel culture. These coastal environments are huge attractive areas to the mussel growing where both the growing and production of mussel seed have a high potential. The bibliographical research has approached aquiculture, mussel growing and public health aspects. Despite the importance fishing has to the planet s food security, the serious world fishing storage run-out supply still exists. With the Brazilian fishing activity s decline and the economical and environmental unsustainable shellfish craft extractives, the mussel culture has been gaining much importance as an alternative of job and income for reduced purchase power fishing communities. However, the mussel culture can generate significative social conflicts and environmental impacts in coastal zones, as well as suffer human locally and hydrographic-bay course effects, threatening marine environment regions with mussel culture potential. Most of the cases are sanitary problems caused by wastewater, industrial and residential wastes eviction, directly in the aquatic environment, with no previous proper treatment. The shellfish, as they are excellent water filterers, are used as biological indicators of that human effect, as they concentrate marine ecosystem contaminator. For that reason the mussel flesh consumption out of the sanitary regulamented standards may bring a countless amount of pathogens to the human being, ending up becoming a risk to public health. In what it concern mussel culture sanitary aspects, important norms of Ministério da Saúde, do Ministério da Agricultura, Pecuária e Abastecimento e do Ministério do Meio Ambiente are brought out. The used methodology was descriptive and correlational survey of facts and the phenomenon of researched areas, due to the complexity of the surveyed aspects. In Itaipu, 25 questionnaires were applied to a universe of 200 fishermen properly registered in the Z-7 Itaipu/Maricá fishermen colony, which are used to disembark and trade the fishing at Itaipu inlet. In the Jurujuba inlet, through the Associação Livre de Maricultores de Jurujuba, some interviews were made with 27 of its associates, representing a universe of 80 properly registered fishermen. Under this focus, secondary date survey, formulation and submit of closed questionnaires to the social actors were used. The questionnaires results, after statistical treatment (qui-square), and the characterization of the survey areas by secondary data have revealed those actors profile in relation with the social-economical, sanitary, environmental aspects and the perception of mussel culture. The feeding and ordering of mussel culture in those survey areas, by Public Empowerment, should incorporate bioethics principles in the search for social environmental sustainability of the fishing communities of Itaipu and Jurujuba